THE CONSTITUTION OF UKRAINE, CODIFIED LEGISLATIVE ACTS AND LAWS OF UKRAINE AS SOURCES OF NATURAL RESOURCES LAW - Mustafina , Valeriia (Collection of scientific papers «ΛΌГOΣ», 2025)
Natural resource law is a sub-branch of environmental law that regulates social relations on the protection and rational use of certain types of natural resources: land, subsoil, water, atmospheric air, climate resources, airspace, radio frequency resources, flora and fauna, and alternative energy sources.